What Drosophila can tell us about state-dependent peptidergic signaling in insects - Nässel, Dick R. (Insect biochemistry and molecular biology, 2025)
Plasticity in animal behavior and physiology is largely due to modulatory and regulatory signaling with neuropeptides and peptide hormones (collectively abbreviated NPHs). The NPHs constitute a very large and versatile group of signaling substances that partake at different regulatory levels in most daily activities of an organism. This review summarizes key principles in NPH actions in the brain and in interorgan signaling, with focus on Drosophila. NPHs are produced by neurons, neurosecretory cells (NSCs) and other endocrine cells in NPH-specific and stereotypic patterns. Most of the NPHs have multiple (pleiotropic) functions and target several different neuronal circuits and/or peripheral tissues. Such divergent NPH signaling ensures orchestration of behavior and physiology in state-dependent manners. Conversely, many neurons, circuits, NSCs, or other cells, are targeted by multiple NPHs. This convergent signaling commonly conveys various signals reporting changes in the external and internal environment to central neurons/circuits. As an example of wider functional convergence, 26 different Drosophila NPHs act at many different levels to regulate food search and feeding. Convergence is also seen in hormonal regulation of peripheral functions. For instance, multiple NPHs target renal tubules to ensure osmotic homeostasis. Interestingly, several of the same osmoregulatory NPHs also regulate feeding, metabolism and stress. However, for some NPHs the cellular distribution and functions suggests multiple unrelated functions that are restricted to specific circuits. Thus, NPH signaling follows distinct patterns for each specific NPH, but taken together they form overlapping networks that modulate behavior and physiology. [Display omitted] •Numerous neuropeptides serve in regulation of insect behavior and physiology.•Neuropeptides and peptide hormones (NPHs) are produced by stereotypic sets of neurons.•Peptide signaling is local or global depending on type of NPH and expression pattern.•NPHs are pleiotropic and can have multiple targets (neurons and tissues).•Multiple NPHs may converge on a neuronal circuit or peripheral tissue.